Auction and contracting mechanisms for channel coordination with exponential demand functions. (2nd July 2016) - Guo, Wei; Ma, Cheng
Abstract: This paper considers a supply chain system with two competing suppliers providing identical products or service to a retailer incorporating risk attitudes. The risk attitude is quantified using the value-at-risk measure and the retailer faces a stochastic exponential price-dependent demand function. Several simple situation and auction mechanisms are developed and compared. The results show that, for auction and two-part contracting mechanisms, the retailer and the low-cost supplier are cooperating together to maximize the total profit of the supply chain with complete information and asymmetric information; however, in this simple situation without complicated auction, the channel-coordinated system optimums cannot be achieved.